Dehydration and storage studies of indigenous shrimps [Palaemon (Nematopalaemon) tenuipes] of Cagayan - Chua, Wilma Q. (College of Fisheries, University of the Philippines in the Visayas, 1989)
Indigenous shrimps of Cagayan locally called "aramang" was identified by the Natioanl Museum to belong to the Family Palaemonidae, Genus Palaemon (Nematopalaemon) tenuipes (Henderson, 1893). The dying parameters for shrimps such as temperature (35 C, 45 C, 55 C), air velocity (05 mps, 1.0 mps, 1.5 mps), drying layer thickness (0.5 cm, 1.5 cm, and air flow direction (upward, downward) were studied. Results indicated the drying parameter combination of 45 C - 0.5 cm thickness 1.0 mps - upward air flow was appropriate for dying the shrimp species. The shrimps dried in approximately 4 hours to a final moisture content (MC) of 20%. At the end of the three-month storage period, artificially dried shrimps packed in carton and polyethylene bags showed mean acceptability scores of 5.8 and 6.2, respectively at 10 C ; while at 28 C, the mean scores were 5.3 and 5.7 for the carton and polyethylene, respectively. Polyethylene bags used as packaging material proved significantly better than carton.. In sundried samples, storage at 10 C in carton and polyethylene showed a maximum shelf-life of 2.5 months.whereas, at 28 C, it was 2.25 months. At 28 C, the samples stored in PE were rejected with a score of 4 when the MC, AW, Astacene, TVN and ammonia contents were 18.83, 0.74, 1.25, 113.37 and 86.40, respectively. Similarly, samples packed in carton were rejected when these values were 15.49, 0.672, 1.37, 107.95, and 85.01, respectively.. At storage temperature of 10 C, these values were 18.07, 0.724,1.65, 111.59 and 86.44 for samples in PE, whereas, in carton, these were 9.02, 0,439, 89.52 and 84.06, respectively.